STABILITAS TANAH LEMPUNG DENGAN SERBUK CANGKANG KERANG TERHADAP NILAI KUAT GESER - Ikhwan Ardi; Gusneli Yanti; Muthia Angraini (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
Soil stability is one of the efforts to increase the carrying capacity of the soil. Clay soils with high plasticity have the potential to become problematic soils because they have low bearing strength and high shrinkage expansion. One of the methods to increase the bearing capacity is the stabilization of clay soil using Shellfish Powder. This study aims to determine the value of the shear strength of clay with the addition of shells powder. The land used is from Jalan Gunung Sari, District of Rumbai, Pekanbaru City. The research method used in this research is an experimental method. The experiment was carried out by mixing the original soil with clam shell powder with variations of a mixture of 0% 5%, 10%, 15% and 20% then the sample is tested using the Direct Shear tool, the method used is the Direct Shear Test (SNI 3420:2016). The results showed that the greater the variation of shell powder, the shear stress, cohesion and shear angle increased. The value of shear stress, cohesion and shear angle of the original soil obtained a shear stress value of 0.6218 kg/cm2, a cohesion value of 0.3478 kg/cm2, and a shear angle of 24.65Â°. The value of the highest shear stress, cohesion and shear angle at the addition of stability is 20% with a shear stress value of 0.6995 kg/cm2, a cohesion value of 0.3905 kg/cm2 and a shear angle of 27.30Â°. The conclusion of this research is the value of shear strength of clay with the addition of shells powder can increase the value of shear strength and bearing capacity of clay.